2007
DOI: 10.1071/bt06063
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal tolerance in common fern species

Abstract: The effects of cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni), lead (Pb) and zinc (Zn) on the growth and uptake of 10 fern species was investigated under a controlled environment in order to evaluate their suitability for phytoremediation. Fern species included Adiantum aethiopicum, Blechnum cartilagineum, Blechnum nudum, Calochlaena dubia, Dennstaedtia davallioides, Doodia aspera, Hypolepis muelleri, Nephrolepis cordifolia, Pellaea falcata and the arsenic (As) hyperaccumulating Pteris vittata. Ferns we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…Significantly greater accumulation of Cr and Fe occurred in roots than in leaves, suggesting limited mobility and translocation of these metals once absorbed by T. vulgare . Sequestration of metals in roots enables plants to continue uninhibited growth, and it is an important mechanism of metal tolerance (Kachenko et al 2007). These results are in agreement with Page (2002) and Olivares et al (2009), i.e., that Cu, Mn, and Zn are essential plant micronutrients, and their uptake and allocation in plant organs, such as photosynthetic tissues, is high and active.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly greater accumulation of Cr and Fe occurred in roots than in leaves, suggesting limited mobility and translocation of these metals once absorbed by T. vulgare . Sequestration of metals in roots enables plants to continue uninhibited growth, and it is an important mechanism of metal tolerance (Kachenko et al 2007). These results are in agreement with Page (2002) and Olivares et al (2009), i.e., that Cu, Mn, and Zn are essential plant micronutrients, and their uptake and allocation in plant organs, such as photosynthetic tissues, is high and active.…”
Section: Resultsmentioning
confidence: 99%
“…This is not surprising as this wetland species has been noted to be one of the plants that are ubiquitous in contaminated soils, particularly in mining areas (Kubicka et al, 2015;Samecka-Cymerman et al, 2012). Kachenko et al (2007) also reported that translocation of some metals was limited in P. aquilinum because of absorption and retention in roots, suggesting an exclusion mechanism as part of its tolerance to the metals which is a major factor in phytostabilization. S. nodiflora seems to phytostabilize Pb, Ni and Cr and A. tectorum possesses the potential to stabilize Zn, Pb and Cd.…”
Section: Level Of Metal In Tissue Biomass Of the Native Speciesmentioning
confidence: 98%
“…Namun, ada beberapa jenis tumbuhan yang toleran terhadap logam berat, seperti Nephrolepsis cardifolia, Hypolepsis muelleri dan Pteris vittata. Menurut Kachenko et al (2007), ketiga spesies tumbuhan paku tersebut toleran terhadap logam berat (Cu, Pb, Ni, Zn, Cd dan Cr) dan potensial sebagai phytostabilizer pada tanah yang terkontaminasi logam berat. Jenis tumbuhan lain yang toleran terhadap logam berat adalah tumbuhan dominan yang dapat tumbuh dengan baik di areal bekas tambang yang tercemar limbah logam berat dan berpotensi sebagai fitoremediator seperti Cyperus sp., Lycopodium sp., dan Melastoma sp.…”
Section: Pendahuluanunclassified